Teaching a foreign language for professional purposes: peculiarities of legal terms used in teaching the language of a speciality for international specialists - Samorodova, Ekaterina; Belyaeva, Irina; Birova, Jana; Ogorodov, Mikhaïl (Journal of Education Culture and Society, 2021)
Aim. One of the most important tasks which precedes the setting of goals for teaching a foreign language of a specialty and the selection of methods for achieving them is to identify the competencies that a qualified specialist must master. Therefore, the authors of this article see the need to set the following research tasks: the identification of professional competencies in the professional discourse of international affairs; the allocation of competencies among those that require the knowledge of a foreign language; and determination of the language material necessary for studying the specialty in the language lessons for international affairs.Methods. The empirical methods of our research comprise studying and analysis of the works of Russian and foreign scientists and teachers working in the related fields; and interviewing specialists in the international sphere who have graduated from the faculties and institutes of international relations, international law, world politics and economics in the form of an anonymous questionnaire. Theoretical methods include analysis, synthesis, comparison, generalisation, deduction, and induction.Results. A study based on the analysis of a survey completed by international specialists showed that a large number of professionals in the field of international relations, international law, politics, and economics use legal terminology in their work more often than others. Among the professional skills that are required in their work, the respondents named negotiation, business dialogue, and correspondence.Conclusion. A recent study has shown that disciplines such as international law must be included in the language training program for international specialists as diplomates and lawyers.